2021
DOI: 10.1016/j.gca.2020.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Nebular thermal processing of accretionary fine-grained rims in the Paris CM chondrite

Abstract: Fine-grained rims (FGRs) are ubiquitous in chondrites. They consist of unequilibrated mineral assemblages that surround chondrules and refractory inclusions. As such, they carry information about the material that was accreted onto chondrules. To decipher the nature and the formation mechanism of FGRs and compare them to adjacent matrix material, we investigated their composition, mineralogy, density and texture in the pristine Paris CM chondrite. We coupled a new method (ACADEMY; Zanetta et al., 2019) at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(74 citation statements)
references
References 83 publications
(167 reference statements)
9
65
0
Order By: Relevance
“…Our scenario also indicates that inner rims formed in a hotter environment than outer rims. This would be consistent with the observed characteristics of inner rims (e.g., silicate sintering, sulfides growth, and compaction; Zanetta et al 2021).…”
Section: Rim Formation Without Erosionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our scenario also indicates that inner rims formed in a hotter environment than outer rims. This would be consistent with the observed characteristics of inner rims (e.g., silicate sintering, sulfides growth, and compaction; Zanetta et al 2021).…”
Section: Rim Formation Without Erosionsupporting
confidence: 87%
“…The majority of studies assumed that FGRs were formed via the accretion of dust particles onto the surfaces of chondrules/CAIs in the turbulent solar nebula (e.g., Metzler et al 1992;Morfill et al 1998;Cuzzi 2004;Xiang et al 2019Xiang et al , 2021Matsumoto et al 2021;Kaneko et al 2022). This nebular scenario naturally reproduces the positive correlation between the rim thickness and the chondrule radius, which is reported for FGRs around chondrules in CM chondrites (e.g., Metzler et al 1992;Hanna & Ketcham 2018;Zanetta et al 2021).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Mounting evidence suggests that FGRs, or their immediate precursors, formed in relatively warm environments. Indeed, Zanetta et al (2021) reported that, despite their porosity, FGRs in Paris show low degree of aqueous alteration, which they attributed to low water/rock ratios, as expected if water was mostly gaseous at the time of FGR formation (and if water mobility was limited to a few tens of micrometers on the parent body after accretion; Brearley, 2014). Bigolski (2017) has found that most FGRs around UOC chondrules exhibit sintered textures and estimated a range of 350-800 °C for their formation.…”
Section: Fgr and Chondrule Formationmentioning
confidence: 99%
“…However, FGRs and the matrix exhibit different presolar grain abundance and alteration degree (e.g. Leitner et al, 2016;Haenecour et al, 2018;Zanetta et al, 2021). FGRs may have been formed soon after or during chondrule forming events (e.g.…”
Section: Expected Structures Of Fgrsmentioning
confidence: 99%